Knocked up [videorecording (DVD)] - Apatow, Judd, 1967-; Rogen, Seth, 1982-; Goldberg, Evan; Heigl, Katherine; Rudd, Paul; Mann, Leslie, 1972-; Baruchel, Jay, 1982-; Hill, Jonah, 1983-; Segel, Jason, 1980-; Starr, Martin, 1982-; Ramis, Harold; Kerns, Joanna, 1953-; et al. (Universal Studios Home Entertainment, 2007)
Ben is a 23-year-old slacker who meets up and coming career girl Alison at a bar. They end up having a one night stand. Eight weeks later, Ben is shocked when Alison meets him and reveals that she is pregnant. Despite having little in common, the two decide that they have to at least try to make some kind of relationship work for the baby's sake.